2004
DOI: 10.1021/jp047900c
|View full text |Cite
|
Sign up to set email alerts
|

Electron Transfer through H-bonded Peptide Assemblies

Abstract: A series of ferrocene (Fc)- and cystamine (CSA)-labeled peptides of the sequence [Fc-(Pro-Pro-Gly) n -CSA]2, where n = 1−3, was synthesized and characterized. Peptide 3 forms a trimeric supramolecular structure held together with extensive hydrogen bonding and adopts a collagen-like motif in solution. Cyclic voltammetry (CV) and chronoamperometry (CA) were used to calculate electron-transfer (ET) kinetics. ET rates were 10.9 (2.3) × 103, 6.6 (1.9) × 103, and 4.2 (1.2) × 103 s-1 for peptides where n = 1, 2, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
91
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(96 citation statements)
references
References 92 publications
5
91
0
Order By: Relevance
“…Hydrogen bonding could induce stable secondary structures which might assist electron transfer reactions. [37,38] Hole hopping along amide groups [39,40] in a-helices composed of Ala and a-aminoisobutyric acid (Aib) has been shown to be efficient over long distances. [41] Attempts to understand and exploit conformations and electronic interactions in oligoamides composed of ferrocenes are subjects of the following report.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogen bonding could induce stable secondary structures which might assist electron transfer reactions. [37,38] Hole hopping along amide groups [39,40] in a-helices composed of Ala and a-aminoisobutyric acid (Aib) has been shown to be efficient over long distances. [41] Attempts to understand and exploit conformations and electronic interactions in oligoamides composed of ferrocenes are subjects of the following report.…”
Section: Introductionmentioning
confidence: 99%
“…Especially, electron transfer through helices has attracted much attention because it is believed that α-helical segments play an essential role in mediating an electron and determining its direction in biological systems [6]. To study the nature of electron transfer, radiolysis [7,8] and photoinduced electron-transfer [9] studies in solution (donor-peptide-acceptor), electrochemical studies on self-assembled monolayer (SAM) systems (donor-peptide-metal) [10][11][12][13][14][15], and recently, single molecule measurements by scanning probe microscopy (metal-peptide-metal) [16][17][18], have been conducted intensively. Most of the researchers agree that a helical peptide is a good electron mediator and enables electron transfer over a long distance.…”
Section: Introductionmentioning
confidence: 99%
“…We thus suggested that a hopping mechanism with amide groups as hopping sites was responsible for this long-range electron transfer. Kraatz and co-workers studied a similar monolayer system with Pro-based peptides carrying a ferrocene moiety at the terminal, and they observed a very weak distance dependence that could be attributed to hopping [12,13]. Recently, however, they have emphasized the importance of molecular dynamics whether the electron transfer is governed by tunneling or hopping [14].…”
mentioning
confidence: 99%
“…Our electrochemical measurements by CV and CA in H 2 O and D 2 O, allowed us to evaluate the ET kinetics (see Figure 8). [21] A linear and shallow distance dependence of k ET on film thickness was found. Furthermore, our ET studies in D 2 O show that the ET rates are slower and a kinetic isotope effect (KIE) of 1.2 to 1.6 was observed.…”
Section: Electron Transfer Studies Of Peptides On Surfacesmentioning
confidence: 87%